2010
DOI: 10.1089/ten.tea.2009.0286
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection of Biocompatible Alginates for Islet Encapsulation and Subcutaneous Transplantation

Abstract: Islet encapsulation requires several properties including (1) biocompatibility, (2) immunoprotection, and (3) oxygen diffusion for islet survival and diabetes correction. New chemical alginates were tested in vivo and compared with traditional high-mannuronate and -guluronate alginates. New alginates with coupled peptide sequence (sterile lyophilized high mannuronate [SLM]-RGD3% and sterile lyophilized high guluronate [SLG]-RGD3%), to improve encapsulated cell adherence in the matrix, and alginates with a very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 54 publications
2
66
0
Order By: Relevance
“…Thus, there is a need to confirm that the capsule possesses permeability to molecules of low molecular weight such as glucose, nutrients, insulin and metabolites (<75 kDa). The immunoglobulin molecular weight limits are 150, 500 and 800 kDa for IgG, activated complements and IgM, respectively (Vériter et al, 2010). To this end, 100 to 200 μm alginate capsules were used to confirm the penetration of variously sized dextrans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a need to confirm that the capsule possesses permeability to molecules of low molecular weight such as glucose, nutrients, insulin and metabolites (<75 kDa). The immunoglobulin molecular weight limits are 150, 500 and 800 kDa for IgG, activated complements and IgM, respectively (Vériter et al, 2010). To this end, 100 to 200 μm alginate capsules were used to confirm the penetration of variously sized dextrans.…”
Section: Discussionmentioning
confidence: 99%
“…Yun et al (63) have reported that PEG-based chemical immunomodulation can provide a semi-permanent effective therapy that protects transplanted islets at least for 1 year when accompanied by cyclosporine. Furthermore, Vériter et al (58) have tested originals alginates with respect to sterile lyophilized high mannuronated and they have had an optimum result with high mannuronated with high viscosity alginate.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, direct measurement of oxygen levels within microencapsulated devices in vivo has not been previously reported, where such measurements are ultimately required to assay the efficacy of implant technologies that claim to promote oxygen delivery. In a study of relatively large alginate disc implants (1 to 1.5 cm 2 surface area at 3-to 6-mm thick) by Veriter et al, 18 oxygen within implanted devices was directly measured through the use of electronic paramagnetic resonance oximetry in rats. However, current research shows that such thick devices cannot retain islet function, likely due to diffusional limitations, thus promoting microencapsulation technologies such as thin sheets or microbeads of permeable materials.…”
Section: Introductionmentioning
confidence: 99%